How Should Financial Institutions and Markets be Structured? Analysis and Options for Financial System Design - George G. Kaufman; Randall S. Kroszner (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper analyzes the consequences of alternative financial structures for financial efficiency and stability. The focus is on the organizational structure of banks. Alternative bank structures range from `narrow banks` to broad `universal banks. ` Each banking structure is assessed in its ability to satisfy the objectives of efficiency and stability in the financial system stability, economies of scale and scope, competition, avoiding regulatory capture, conflicts of interest and political manipulation, corporate control and management of financial distress, and monetary control. No one reform is appropriate for all countries, and no single reform guarantees that the objectives will be attained or maintained.
Keywords: 330